ANALYSIS OF COMPETENCE-BASED DEVELOPMENT OF CIVIL SERVANT RESOURCES AT THE BPS OF RIAU ISLANDS PROVINCE - Manurung, Herdinawaty; Wijaya, Andy Fefta; Novita, Asti Amelia (Faculty of Administrative Science, Universitas Brawijaya, 2024)
This study aims to describe and analyze the development of competency-based civil servant resources at BPS Riau Islands Province, as well as to identify factors that support and hinder the implementation of competency development. This study uses Spencer and Spencer's (1993) competency theory which states that competence consists of five main components, namely knowledge, skills, motives, self-concept, and nature/character. This study uses a qualitative descriptive approach. Research data were collected through interviews as primary data, while secondary data were collected through the BPS Riau Islands Province personnel database and reports related to the research and also through other literature such as books, journals, and other related research. The results of the study indicate that the development of civil servant resources at BPS Riau Islands Province has included various training programs that focus on improving statistical technical knowledge and skills. However, aspects of developing motives, self-concept, and nature/character have not been fully integrated into the program, thus impacting the effectiveness of competency development which is not yet optimal. The supporting factors identified include the commitment of leaders and management to competency development, the existence of Government Regulations/Rules, the availability of good and adequate training infrastructure including e-learning access, and the human resources of the Riau Islands Province BPS who are still of productive age also become supporters. On the other hand, the inhibiting factors faced include budget limitations, the absence of a sustainable development evaluation system, development activities have not been carried out based on training analysis needs analysis, and the low interest and motivation of employees to participate in development.